2007
DOI: 10.1179/136485907x176463
|View full text |Cite
|
Sign up to set email alerts
|

Cercarial dermatitis in central India: an emerging health problem among tribal communities

Abstract: Although cercarial dermatitis is an emerging disease world-wide, cases of such dermatitis may often go undiagnosed, especially in communities that are affected by various skin infections. Between August 2001 and July 2002, 1336 individuals from tribal villages in central India were examined for dermatitis. Skin scrapings were collected and examined for Sarcoptes scabiei and each subject's response to antiscabies treatment was recorded. Freshwater snails were collected from the local ponds used for bathing, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Most reported cases of dermatitis caused by the genus Schistosoma are from parasites that infect domesticated work animals, such as cattle and buffalo, mainly in Asia. For example, in countries such as India and Nepal, the species Schistosoma turkestanicum, Schistosoma nasale, Schistosoma indicum, and Schistosoma spindale are often implicated in outbreaks of dermatitis (29)(30)(31)(32)(33)(34)(35)(36)(37)(38). This relationship may not be a surprise, as bovids are the definitive host, and the people in these areas depend upon these animals for their livelihood in farming.…”
Section: Diversity Of Schistosomes Causing Dermatitismentioning
confidence: 99%
“…Most reported cases of dermatitis caused by the genus Schistosoma are from parasites that infect domesticated work animals, such as cattle and buffalo, mainly in Asia. For example, in countries such as India and Nepal, the species Schistosoma turkestanicum, Schistosoma nasale, Schistosoma indicum, and Schistosoma spindale are often implicated in outbreaks of dermatitis (29)(30)(31)(32)(33)(34)(35)(36)(37)(38). This relationship may not be a surprise, as bovids are the definitive host, and the people in these areas depend upon these animals for their livelihood in farming.…”
Section: Diversity Of Schistosomes Causing Dermatitismentioning
confidence: 99%
“…Although it is an emerging water-borne non-communicable disease prevalent among rural and tribal population of India, it is often neglected, unrecognized and under-reported owing to lack of access to adequate diagnostic & health care facilities [5]. Usually non-human schistosomes (birds and animal schistosome) are mainly attributed to this intense inflammatory pruritic skin condition.…”
Section: Cercarial Dermatitis In Indiamentioning
confidence: 99%
“…When cercaria of these parasites emerge from their snail hosts and penetrate skin of patients, they induce inflammatory response to eliminate parasites trapped in the skin [12]. In a recent study, the prevalence of it varied from 2.1% and 12.5% during the year with highest infection rate during winter and the rainy season [5]. Agarwal et al, have reported incidence of cercarial rash in Jabalpur, Madhya Pradesh which was unrecognized and misinterpreted by health practitioners and local people [39].…”
Section: Cercarial Dermatitis In Indiamentioning
confidence: 99%
See 1 more Smart Citation
“…n recent years, waterborne outbreaks of cercarial dermatitis, also known as swimmer's itch, have increasingly been reported worldwide (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Cercarial dermatitis is caused by free-swimming cercariae of avian and mammalian schistosomes emerging from snails that penetrate and die within human skin, causing an inflammatory immune response (12).…”
mentioning
confidence: 99%